What is the Role of Organizational Culture, Competence and Motivation on the SMEs Performance in the Digital Era and the Covid-19 Pandemic? - Suryoto, Suryoto (IJOSMAS, 2022)
The purpose of this study is to identify the influence of Organizational Culture, Competence and Motivation on the SMEs Performance in the Digital Era and the Covid-19 Pandemic. This research method is quantitative through online surveys through online social media. The sampling technique used was purposive sampling technique with the number of samples determined as many as 130 SMEs staff respondents. The quantitative data analysis technique used partial least square structural equation modeling (PLS-SEM) analysis. Based on the results of calculations using PLS-SEM software version 3.0, the results of this study are: The organizational culture has a positive and significant effect on the performance of SME employees. Companies can strengthen organizational culture to improve employee performance. Competence variable has a significant and positive effect on the performance of SMEs. The motivation variable has a positive and significant eefect on the performance of SME employees. By providing motivation to employees both materially and morally will increase employee morale at work. Simultaneously there is a significant influence positive and significant relationship between organizational culture, competence and motivation variables towards SME employee performance